Essential spectra of non-collective ordinary differential operators with complex coefficients - Erovenko, B. A. (Mathematical Modelling and Analysis, 1996)
“Существенные спектры несамосопряженных обыкновенных дифференциальных операторов с комплексными коэффициентами”Mathematical Modelling Analysis, 1(1), p. 21-24.Article in Russian.First Published Online: 14 Oct 2010